Sosialisasi Pencegahan Stunting dan Edukasi Parenting di Desa Argosari Kabupaten Malang - Siti Rodliyah Eka Agustina; Annisa Surya Cahyaning Akhfa; Icha Amelia Agustin; Risa Nur Faizatur Rohmah; Irma Meiliya; Tazkiatun Nafs Azzahro; Andini Wardaniyah Putri; Wahyudi Saputra Irawan; Muhammad Fikri Afif; Mohammad Zainul ‘Ibad Romadhon; Fatmawati Zahroh (Unika Santu Paulus Ruteng, 2023)
The socialization aims to provide information about stunting prevention and parenting education to mothers in Argosari Village, Jabung District, Malang Regency. The observation results show that there are still toddlers who experience stunting. The method of implementing this activity is interactive socialization. This socialization was filled by two KKN students who were in accordance with their fields. Through socialization activities, it is hoped that mothers can understand stunting, how to prevent stunting, routinely attend posyandu, and understand parenting according to the needs of each family.